Time's enchantment & other reflections - Kilates, Marne (Naga City, Philippines Ateneo de Naga University Press, 2014)
"Time's Enchantment & Other Reflections is award-winning poet Marne Kilates's new collection ranging over old and new themes of his idyllic childhood in the province and the nightmare of his hometown catching up with the urban mayhem of his adult life."--Back cover.
Diaphanous -- Dedication -- In the garden -- Bookmarks -- A discourse of red -- Sea bliss in Bolinao -- Carabao English -- A fire in the town -- Cat -- Partitas : Anastacio & Miring -- Mayon -- Reunion (I) -- After watching "The Chase of Benyaki" -- Oriental eisteddfod -- Asians at the Museo del Prado -- Garland : Sampaguita -- Barcelona -- Goya's war -- Velasquez's mirrors -- The panels of Hieronymus Bosch -- My David's head -- Reunion (II) -- Il porcellino -- In memoriam -- The jukebox from Mars -- The jukebox from Venus -- The Palawan mermaid -- Fan/kabkab -- Sibubog, gin, and kalamansi -- Communion wafers -- Arturo Luz -- Miring's enchantment -- Cat's cradle -- "A collision in Saturn's rings" -- La dicha -- Tiyong Andoy carries the San Antonio -- Time's enchantment -- From a time strange to us -- Brats -- Old houses -- Houses : a history -- Sand painter -- Aying & Bebang in Li-bog, 1895 -- The park -- "Way over my head" -- Elegy for Joel -- Ghost in the house of ruin -- The billboards are burning! -- Tiyong Andoy woos Tiyang Cading -- To the armless Christ in a ruin in Guiuan -- My marinae -- Hard hats -- Sixteen ways of looking at Monet's water lilies -- Reunion (III) -- Tiyong Jose, Sanidad -- Postman -- All these wars -- Balicucha -- Milk nougat -- Amado & Loleng -- Brisk-walking haikus -- Memory sometimes tricks us -- Insipit -- Handyman -- Reunion (IV) -- Don Belong at Montjuich & my artificial memory -- Morning moon -- Time's mystery -- Ghazal of the bleeding heart -- Ghazal of the Kamuning -- Mabini in exile -- The house on No. 5 Sta. Theresa Street -- Road to Sagada -- Hunting for pinikpikan and etag -- Litany of the Benguet Lily -- Polar bear -- Marne Kilates -- Kind and dangerous words for Kilates' poetry.
Keywords: Philippine poetry (English)